2002 IEEE International Solid-State Circuits Conference. Digest of Technical Papers (Cat. No.02CH37315)
DOI: 10.1109/isscc.2002.992971
|View full text |Cite
|
Sign up to set email alerts
|

A 300 MHz quadrature direct digital synthesizer/mixer in 0.25 μm CMOS

Abstract: The frequency synthesis and mixing operation of Equation (1) accepts an input sequence with x-y coordinates [X I (n), Y I (n)] and an input frequency control word f, producing the output sequence [X O (n), Y O (n)].(1)The common implementation of (1) employs a DDFS to generate sin(2πnf) and cos(2πnf), feeding a complex multiplier (mixer) (Figure 7.5.1). Most DDFS architectures use lookup tables with pre-computed stored sine and cosine values. The exponential dependence between table size and phase word-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…It is shown that, given an overall output precision requirement, the size of all arithmetic components can be accurately determined to satisfy such a requirement while using minimal hardware. The theory, architecture and error analysis developed here support recently reported integrated circuit implementations [6]- [8]. Other two-stage DDS/mixer implementations, also employing small ROMs along with computational circuitry, have recently appeared [9], [10].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…It is shown that, given an overall output precision requirement, the size of all arithmetic components can be accurately determined to satisfy such a requirement while using minimal hardware. The theory, architecture and error analysis developed here support recently reported integrated circuit implementations [6]- [8]. Other two-stage DDS/mixer implementations, also employing small ROMs along with computational circuitry, have recently appeared [9], [10].…”
Section: Introductionsupporting
confidence: 62%
“…Simulations and, more recently, the design, fabrication and testing of an integrated circuit prototype [6], [7] (and [8] for a one-output system), have verified that in comparison to one of the best prior implementations of a single-stage digital mixer [1], optimized for a 14-bit input angle, the two-stage method presented here achieves a 6-dB better SFDR while using a comparable amount of circuitry. In addition, since the two-stage structure employs only a small ROM, it overcomes the problem of slow access time that can occur when large ROMs are used, thereby facilitating a higher data rate.…”
Section: Discussionmentioning
confidence: 76%
“…In order to exactly rotate by , a full-precision complex multiplier is needed. However, the coarse rotation does not need to be exact, because the coarse rotation error, if it exists, can be corrected by the fine rotation [7]. Fig.…”
Section: Alternative Implementationmentioning
confidence: 99%
“…In order to reduce the spurious tones, a significant number of iterations and high resolution of the datapath are required. Using a computational algorithm and a lookup table in a combined approach can offer better optimization in hardware complexity and speed [6], [7]. Further reduction of the lookup table size is desired as the implementation cost of a digital communication system becomes more important.…”
Section: Introductionmentioning
confidence: 99%
“…The most critical stage in a DDFS is the PSAC. Many prior works for improving the performance of PSAC include angular decomposition techniques [1,[3][4][5][6], angle rotation methods [7][8][9], polynomial approximations [10][11][12], and sine amplitude compression methods [13][14][15][16]. In the sine amplitude compression methods, they only use linear approximations to decrease a ROM size.…”
Section: Introductionmentioning
confidence: 99%